'I (do not) know what to do': how ties, identities and home states influence Mexican-born immigrants' return migration intentions. (2nd September 2018) - Tezcan, Tolga
Abstract: This study examines the return migration intentions of Mexican immigrants to the U.S. by proposing three explanatory variables: (1) socioeconomic ties with the U.S. and Mexico, (2) ethnic identity, and (3) the human development levels of origin home states in Mexico. Utilizing the 2006 Latino National Survey, which included 3743 Mexican-born immigrants to the U.S., I developed a multilevel multinomial logistic regression model to distinguish between potential returners, potential stayers, and those who were undecided. While socioeconomic ties with the U.S positively predict staying intentions, socioeconomic ties with Mexico are positively related to intentions to return as well as with indecision. Self-identification as Latina/o or Hispanic is not associated with return migration intentions, while self-identification as Mexican and American is. Other components of ethnic identity, such as skin colour and co-ethnic friendship ties, are also associated with return intentions. Additionally, Mexican immigrants whose home states in Mexico have higher levels of human development are less likely to form return intentions and indecision.